Pengaruh Model Pembelajaran Berbasis Masalah Terhadap Hasil Belajar Biologi dan Keterampilan Berpikir Kritis Peserta Didik - Patmawati Patmawati; Yusminah Hala; Muhammad Arsyad (UNM Journal of Biological Education, 2022)
Influence Of Problem Based Learning Model To Biology Learning Outcomes And Critical Thinking Skill Of Students. This research is a quasi experimental with pretest posttest control group design which aims to determine critical thinking skills and learning outcomes. The research sample was randomly selected and the XII IPA 1 was selected as the control and the XII IPA 3 as experimental class. The technique of collecting data was through giving test description to measure critical thinking skills and multiple choice test to measure biology learning outcomes. The data analysis technique used are descriptive and inferential statistics analysis with the independent sample t-test. The result of descriptive analysis show that students who are taught with the model problem based learning have critical thinking skills and learning outcomes in the middle category. While the results of inferential analysis show that there are differences in critical thinking skills and learning outcomes of students who are using the problem based learning model and conventional learning, that show average value of problem-based learning model are higher. The results show the problem based learning model has a positive effect on critical thinking skills and biology learning outcomes in mutation topic at SMAN 10 Luwu Utara.